From colorful forest trails to restoration: a moderated mediation model linking actual and perceived biodiversity to mental well-being - Jin, Wenjin; Gao, Yang; Yang, Hua; Mao, Xikai; Zhang, Hongmei; Chen, Xiaojun; Khan, Waseem Razzaq; Bevilacqua, Stanislao; Shi, Yan (Elsevier GmbH, 2025)
Urban forest trails provide multisensory environments that can restore mental health, yet the psychological pathways linking perceived biodiversity to well-being remain unclear. This study constructs and tests a dual-mediation pathway linking actual biodiversity, driven by vegetation characteristics, to mental well-being, a pathway that has not yet been empirically validated. Field surveys were conducted at nine representative sites along West Lake forest trails in Hangzhou, China, during the peak of autumn foliage. Data from 406 visitors included on-site questionnaires measuring perceived biodiversity, perceived restorativeness, mental well-being, and nature relatedness, with vegetation characteristics measured at the sites on both sides of the trail. Results indicated that while actual biodiversity exerted a negative direct effect on mental well-being, its total effect was significantly positive via the mediating roles of perceived biodiversity and perceived restorativeness. Nature relatedness significantly moderated the first stage of the mediation, amplifying restorative benefits for individuals with stronger nature connections. Vegetation color diversity emerged as the strongest predictor of perceived biodiversity, with plant-related perceptions contributing more than faunal ones (birds and insects). Additionally, walking durations exceeding 60 min were associated with greater well-being gains, indicating a dose–response effect. The study found that nature relatedness (NR) significantly moderates the pathway only for individuals with high NR, with no significant effect for those with low NR. These findings highlight the critical role of perceptual and individual factors in translating biodiversity into psychological benefits. The study provides empirical evidence for biodiversity-sensitive planning that aligns ecological and health objectives in urban landscapes.